Heavy Metal Content in Sediment and Hora Shell (Cerithidea obtusa) in Panipahan Waters, Rokan Hilir, Riau - Indra Wariski; Yusni Ikhwan Siregar; Bintal Amin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2021)
This research was carried out in March 2021 to analyze the heavy metal content of Pb and Cu in the sediment and flesh of the horn shell (Cerithidea obtusa). Sediment samples and horn shells were taken from the coastal waters of Panipahan, Panipahan Village, and Teluk Pulai Village, Rokan Hilir Regency, Riau Province. The method used in this research is a survey method. Sampling was determined by using purposive sampling at three different stations. The results of this study showed that the metal content of Pb and Cu was highest in sediments around residential areas (44.7150 g/g and 104.4200 g/g), while the horn shell was found in areas far from anthropogenic activities (2.4717 g/g and 8.6617 g/g). Differences in the metal content of Pb and Cu in the sediments were found between stations, while for horn shells there was no difference between stations. The metal content of Pb in the sediment did not show a significant effect (F < 0.05) Pb content in horn shells, as well as Cu. The results of the calculation of the PTWI (Provisional Tolerable Weekly Intake) value indicated that the horn shell in the waters is acceptable for consumption.